T7 ejectosome assembly: A story unfolds. Issue 1 (2nd January 2016) - Leptihn, Sebastian; Gottschalk, Julia; Kuhn, Andreas
ABSTRACT: T7 phage DNA is transported from the capsid into the host cytoplasm across the cell wall by an ejectosome comprised of the viral proteins gp14, gp15 and gp16. Prior to infection, these proteins form the so-called internal core in the mature virion. Gp16 was shown to associate with pure phospholipid bilayers while gp15 bound to DNA. A complex of both proteins appears as spiral-like rods in electron micrographs. It was also shown that the proteins gp15 and gp16 have the propensity to regain their full structure after thermal unfolding. From these observations it was concluded that (partial) unfolding of the proteins occurs during the translocation through the narrow portal of the phage capsid. After leaving the phage head, the proteins refold to form the ejectosome channel across the periplasm of the host. In this work, we analyzed the structure of gp15 and gp16 in presence of lipids and their stability toward chemical denaturants. A model to explain how the ejectosome might assemble in the host cell is discussed.